A synthesis of convergent reflections, tensions and silences in linking gender and global environmental change research - Iniesta-Arandia, I.; Ravera, F.; Buechler, S.; Díaz Reviriego, I.; Fernández Giménez, M.E.; Reed, M.G.; Thompson-Hall, Mary; Wilmer, H.; Aregu, Lemlem; Cohen, P.; Djoudi, H.; Lawless, S.; et al. (Springer, 2016)
This synthesis article joins the authors of the special issue "Gender perspectives in resilience, vulnerability and adaptation to global environmental change" in a common reflective dialogue about the main contributions of their papers. In sum, here we reflect on links between gender and feminist approaches to research in adaptation and resilience in global environmental change (GEC). The main theoretical contributions of this special issue are threefold: emphasizing the relevance of power relations in feminist political ecology, bringing the livelihood and intersectionality approaches into GEC, and linking resilience theories and critical feminist research. Empirical insights on key debates in GEC studies are also highlighted from the nine cases analysed, from Europe, the Americas, Asia, Africa and the Pacific. Further, the special issue also contributes to broaden the gender approach in adaptation to GEC by incorporating research sites in the Global North alongside sites from the Global South. This paper examines and compares the main approaches adopted (e.g. qualitative or mixed methods) and the methodological challenges that derive from intersectional perspectives. Finally, key messages for policy agendas and further research are drawn from the common reflection.